EVALUATION OF OCCUPATIONAL HEALTH AND ENVIRONMENTAL SAFETY BASED ON TRI HITA KARANA IN THE PURA AGUNG JAGATNATHA IMPROVEMENT PROJECT - Mahapatni, Ida Ayu Putu Sri; Wirahaji, Ida Bagus; Artana, I Wayan; Pratama, I Putu Gede Angga; Widiantara, I Kadek Bayu (POLITEKNIK NEGERI JAKARTA, 2024)
Implementing occupational health and environmental safety aspects is very important in project implementation. In addition to accelerating work, safety for workers is essential and must be considered. In the implementation of the project in Bali, Tri Hita Karana was carried out to maintain the stability and smoothness of the project. However, limited literature still reveals the relationship between these aspects. This study aims to evaluate and analyze the application model of occupational health and environmental safety based on Tri Hita Karana in the Pura Agung Jagatnatha Improvement Project in Denpasar City. A quantitative research design with a cross-sectional approach was used to evaluate each variable in the Tri Hita Karana component, including Parahyangan (X1), Pawongan (X2), and Palemahan (X3), on occupational health and environmental safety (Y). Two hundred selected respondents were given questionnaires to evaluate each hypothesis. The sampling technique uses total sampling with a research time of 6 months, and the model is analyzed using SEM–AMOS. The results show that the application of the Tri Hita Karana to occupational health and environmental safety has positive and significant consequences (p < 0.05) in the aspects of Parahyangan, Pawongan, and Palemahan. The mathematical model built is Y = 0.548X1 + 0.423X2 + 0.211X3, which means that a change in the Parahyangan value has a direct effect on the application of OHSE by 0.548 times, a change in the value of Pawongan has a direct effect on the application of OHSE by 0.423 times and a change in the value of Palemahan will directly affect the application of OHSE by 0.211 times. Hence, it is hoped that project implementers in Bali will be guided by implementing occupational health and environmental safety based on Tri Hita Karana.